ULAMA AND POLITICS: A Study of Ulama and Santri’s Participation in 2019 General Election in Aceh - Rasyad, Rasyad; Ikhwan, Ikhwan; Manan, Abdul; Putra, Rahmad Syah (State Islamic University North Sumatra, 2022)
Abstract: The existence of ulama and dayah in political dynamics in Aceh has occurred for a long time, simultaneously with the development of Islam in Aceh. Ulama in Aceh has been playing as the main actors behind the successful political indicator in many phases, namely; empire phase, independence phase, new order (orde baru) phase until the phase of reformation. The doctrines played by ulama through religious languages have received great support from people in Aceh. This study employs the qualitative research approach with three main techniques of data collection, namely interview, observation and documentation. The result showed that there has been the participation from ulama and santri dayah in Aceh during 2019 General Election (GE). Such participation was reflected from the full support from ulama by calling up the political machine from santri dayah during 2019 GE, and deciding a political attitude by taking side on one of the candidates by holding a fundamental belief that Islam does not forbid ulama to participate in the political practice. Keywords: ulama, santri, dayah, politics, general election, Aceh